Proposal of Potent Inhibitors for a Bacterial Cell Division Protein FtsZ: Molecular Simulations Based on Molecular Docking and ab Initio Molecular Orbital Calculations - Shohei Yamamoto; Ryosuke Saito; Shunya Nakamura; Haruki Sogawa; Pavel Karpov; Sergey Shulga; Yaroslav Blume; Noriyuki Kurita (MDPI AG, 2020)
The inhibition of a bacterial cell division protein, filamentous temperature-sensitive Z (FtsZ), prevents the reproduction of Mycobacteria. To propose potent inhibitors of FtsZ, the binding properties of FtsZ with various derivatives of Zantrin ZZ3 were investigated at an electronic level, using molecular simulations. We here employed protein-ligand docking, classical molecular mechanics (MM) optimizations, and ab initio fragment molecular orbital (FMO) calculations. Based on the specific interactions between FtsZ and the derivatives, as determined by FMO calculations, we proposed novel ligands, which can strongly bind to FtsZ and inhibit its aggregations. The introduction of a hydroxyl group into ZZ3 was found to enhance its binding affinity to FtsZ.